Screening for type 2 diabetes and periodontitis patients (CODAPT-My©): a multidisciplinary care approach - Abdul Aziz, Aznida Firzah; Mohd Dom, Tuti Ningseh; Mustafa, Norlaila; Said, Abdul Hadi; Ayob, Rasidah; Mohamed Isa, Salbiah; Hatah, Ernieda; Wan Puteh, Sharifah Ezat; Mohd Alwi, Mohd Farez Fitri (Springer Nature, 2022)
Background: The practice of referring diabetic patients for dental intervention has been poor despite awareness and knowledge of the oral health efects of diabetes. Likewise, dentists treating patients receiving diabetes treatment are rarely updated on the glycaemic status and as a result, the opportunity for shared management of these patients is missed. This study aimed to provide a standardised care pathway which will initiate screening for diabetes from dental clinics and link patients with primary care for them to receive optimised care for glycaemic control. Method: A Modifed Delphi technique was employed to obtain consensus on recommendations, based on current evidence and best care practices to screen for diabetes among patients attending dental clinics for periodontitis. Expert panel members were recruited using snowball technique where the experts comprised Family Medicine Specialists (5), Periodontists (6), Endocrinologists (3) and Clinical Pharmacists (4) who are involved in management of patients with diabetes at public and private healthcare facilities. Care algorithms were designed based on existing public healthcare services. Results: The CODAPT© panel recommends referral to primary care for further evaluation of glycaemic status if patients diagnosed with periodontitis record fasting capillary blood glucose levels≥5.6 mmol/L. Intervention treatment options for prediabetes are listed, and emphasis on feedback to the dental healthcare team is outlined specifcally. Conclusion: The CODAPT© care pathway has the potential to link dental clinics with primary care for diagnosis and/ or optimised treatment of prediabetes/diabetes among patients receiving periodontitis treatment. Keywords: Care pathway, Primary healthcare, Dental, Periodontitis, Diabetes, Prediabetes